2010
DOI: 10.1080/17470910903227507
|View full text |Cite
|
Sign up to set email alerts
|

The mere perception of eye contact increases arousal during a word-spelling task

Abstract: Eye contact is a highly salient and fundamentally social signal. This entails that the mere perception of direct gaze may trigger differentiated neurobehavioral responses as compared to other gaze directions. We investigated this issue using a visual word-spelling task where faces under different gaze directions and head orientations were displayed on-screen concomitantly with the words. We show evidence for automatic increase of skin conductance response (SCR), indicative of arousal, associated with the perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(32 citation statements)
references
References 53 publications
0
29
3
Order By: Relevance
“…Some studies have suggested that eye contact elicits arousal/emotional responses (Kawashima et al , 1999; Conty et al , 2010; von dem Hagen et al , 2014), an important feature of the affective arousal model (for a review, see Senju and Johnson, 2009). However, in what situations an arousal/emotional response to eye contact occurs is currently unclear (Mormann et al , 2015; for a review, see Hamilton, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies have suggested that eye contact elicits arousal/emotional responses (Kawashima et al , 1999; Conty et al , 2010; von dem Hagen et al , 2014), an important feature of the affective arousal model (for a review, see Senju and Johnson, 2009). However, in what situations an arousal/emotional response to eye contact occurs is currently unclear (Mormann et al , 2015; for a review, see Hamilton, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…The first account, the ‘affective arousal model’ (Figure 1A), postulates that eye contact elicits responses in brain areas involved in arousal, particularly the amygdala (Kawashima et al , 1999; for a review, see Senju and Johnson, 2009; Conty et al , 2010; von dem Hagen et al , 2014). The second account, the ‘communicative intention detector model’ (Figure 1B), assumes that eye contact signals the intention to communicate with others and involves the theory-of-mind (ToM) network (Kampe et al , 2003; for reviews, see Senju and Johnson, 2009; von dem Hagen et al , 2014), including posterior superior temporal sulcus and/or temporoparietal junction (pSTS&TPJ), medial prefrontal cortex (mPFC) and temporal pole (TP).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, in the affective priming paradigm (Chen et al, 2017a), participants were even instructed to ignore the gaze stimuli, that is, the primes. In fact, the possibility that these discrepant findings are related to attention and cognitive load during stimulus presentation was directly tested in a study by Conty et al (2010). They reasoned that direct gaze might evoke amygdala-mediated autonomic arousal response when face stimuli are presented secondary to a main task.…”
Section: Affective Eye Contact Investigated With Images Versus Live Fmentioning
confidence: 99%
“…There is evidence that viewing another person with a direct gaze elicits greater autonomic arousal than viewing a person with an averted gaze (Nichols and Champness, 1971; Gale et al, 1975; Williams and Kleinke, 1993), even when the face is presented as an irrelevant stimulus during a demanding cognitive task (Conty et al, 2010). We have found enhanced skin conductance responses (SCRs), indicative of autonomic arousal, in response to eye contact with a “live” person and we have suggested that this effect may relate to increased self-awareness in the proximity of another person (Hietanen et al, 2008; Helminen et al, 2011; Pönkänen et al, 2011).…”
Section: Introductionmentioning
confidence: 99%